2018
DOI: 10.2134/jeq2017.08.0314
|View full text |Cite
|
Sign up to set email alerts
|

The Contrasting Effects of Alum‐Treated Chicken Manures and KH2PO4 on Phosphorus Behavior in Soils

Abstract: Alum [KAl(SO)⋅12HO] is often added to chicken manure to limit P solubility after land application. This is generally ascribed to the formation of Al-PO complexes. However, Al-PO complex formation could be affected by the matrix of chicken manure, which varies with animal diet. Alum was added to KHPO (as a reference material) and two manures from typical chicken farms in China, one from an intensive farm (CMIF) and another from free-ranging chickens (CMFR). These were subsequently incubated with soils for 100 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
2
3
0
Order By: Relevance
“…The colorimetrically-determined MRP concentrations in the M3 extracts ranged from 29 to 378 mg kg −1 , representing 47–100% of the P concentrations determined by ICP (Table 5 ). This is also consistent with previous studies [ 9 12 , 14 16 ]. However, previous reports have suggested that the differences between colorimetry and ICP are greater at lower concentrations [ 10 , 12 , 13 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The colorimetrically-determined MRP concentrations in the M3 extracts ranged from 29 to 378 mg kg −1 , representing 47–100% of the P concentrations determined by ICP (Table 5 ). This is also consistent with previous studies [ 9 12 , 14 16 ]. However, previous reports have suggested that the differences between colorimetry and ICP are greater at lower concentrations [ 10 , 12 , 13 ].…”
Section: Resultssupporting
confidence: 94%
“…The ratios of orthophosphate monoesters to diesters (Mono:Diester ratio, Table 6 ) were similar for the control, N and untreated poultry litter (PL) treatments (~ 7), but were lower than the alum-stabilized PL treatment (15.7). This reflects the much higher concentration and percentage of myo -IHP in the M3 extract after alum treatment, which is consistent with previous reports that alum stabilizes myo -IHP in poultry litter, potentially limiting its decomposition or loss in soil [ 15 , 16 , 43 45 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations